The use of serious games for psychological education and training: a systematic review - Facchino, Antonio Pio; Marchetti, Daniela; Colasanti, Marco; Fontanesi, Lilybeth; Verrocchio, Maria Cristina (Frontiers in Education, 2025)
IntroductionThe present systematic review aims to synthesize and critically analyze the use of serious games in the professional training and education of psychologists and psychology students.MethodsFollowing PRISMA guidelines, database searches from inception to July 2023 (PsycINFO, PubMed, Web of Science, and Scopus) yielded 4,409 records, of which 14 met the eligibility criteria, including 17 studies. Quality assessment was performed using the Newcastle-Ottawa Scale and the Risk of Bias Tool for Randomized Trials.ResultsThe review identified three pivotal areas where serious games demonstrated significant educational impact: enhancing psychological traits and attitudes (e.g., prejudice, empathy), promoting theoretical knowledge acquisition (e.g., biopsychology), and developing professional skills (e.g., investigative interview with children). Serious games, particularly those providing feedback and modeling, significantly enhance the quality of learning and training for psychology students and professionals.DiscussionKey findings revealed that serious games operate by offering realistic, engaging, and flexible learning environments while mitigating risks associated with real-world practice. Methodological limitations, including moderate to high risk of bias in many studies, especially those that relied on cross-sectional data, underscore the need for rigorous designs and long-term evaluations. Practical implications suggest integrating serious games into curricula to address gaps in experiential learning for psychologists, facilitating skill development and knowledge retention. Future research should explore the long-term impact of serious games on professional competencies and assess their applicability across diverse educational contexts.